2011
DOI: 10.1007/s13233-011-1203-3
|View full text |Cite
|
Sign up to set email alerts
|

Morphological property and in vitro enzymatic degradation of modified chitosan as a scaffold

Abstract: Chitosan (CS) was proposed as a promising candidate scaffold for tissue engineering. However, some drawbacks of natural CS remain. The current study modified CS by conjugating thiol to CS polymer (Thio-CS) and substantiated its three-dimensional microstructure and physical properties such as swelling or degradation. The Thio-CS was obtained by CS modification using 2-iminothiolane-HCl (2-IT). Because of the formation of disulfide bonds between thiol moieties based on oxidation of the immobilized thiol groups o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…This is consistent with previous report that pore size of substance has direct relationship with the molecular weight of materials [38]. As we reported previously, the optimum ratio between 2-IT and CS for the formation of disulfide bonds is 0.1 mg/mL and 1% (w/v) [34]. However, this ratio does not take account of the air-oxidation time, which can affect the formation of disulfide bonds between CS polymers.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…This is consistent with previous report that pore size of substance has direct relationship with the molecular weight of materials [38]. As we reported previously, the optimum ratio between 2-IT and CS for the formation of disulfide bonds is 0.1 mg/mL and 1% (w/v) [34]. However, this ratio does not take account of the air-oxidation time, which can affect the formation of disulfide bonds between CS polymers.…”
Section: Resultssupporting
confidence: 92%
“…The enhanced bone formation in Thio-CS-B2 might result from more superior property of Thio-CS than Col-gel for bone formation. In our previous report [34], Col-gel showed the limited swelling property with scant physical change of the porosity, suggesting limiting the capacity to absorb BMP-2. The present study also showed that Col-gel-B2 has the burst release pattern of BMP-2 compared with Thio-CS-B2.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations